Coal-based solid waste foaming cement material for coal mine tunnel filling and preparation method thereof
By using coal-based solid waste foam cement materials and combined with physical bubble method, the problem of easy voids in the filling process of coal mine tunnel filling materials is solved, and the lightweight, high-strength, thermal insulation and sound insulation effect of the material is achieved, meeting the requirements for coal mine tunnel filling.
Patent Information
- Application Number
- CN202510118542.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-05-02
AI Technical Summary
In the prior art, the filling materials of coal mine tunnels are prone to voids during the filling process, which affects the filling effect, reduces the support effect of the filling body, and affects the stability of the tunnel.
Coal-based solid waste foam cement material is used to prepare through physical foaming method. The materials include coal-gasified crude slag powder, fly ash, cement, foam stabilizer and additives, and doped with foam. The foam doping amount is 2 to 5 times the volume of cement slurry.
It improves the lightweight and high-strength performance of the filling material, reduces production costs, improves the thermal insulation and sound insulation performance of the material, improves the construction performance and filling quality, and meets the use requirements of coal mine tunnel filling.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of resource utilization of coal-based industrial solid waste, and in particular to a coal-based solid waste foamed cement material for filling coal mine tunnels and a preparation method thereof. Background Art
[0002] Coal-based solid waste refers to solid waste generated during coal mining, processing and conversion, mainly including coal gangue, coal gasification slag, fly ash, etc. The large-scale storage of these solid wastes not only occupies a large amount of land resources, but also may cause environmental pollution and safety hazards.
[0003] Due to the special mining method used in coal mines, in the process of coal mining, the working face often needs to cross unknown old lanes and leftover cross empty lanes. These goaf areas or working face lanes have extremely high requirements for airtightness. If the management of these old lanes is not sufficient, it may cause water seepage, roof collapse, gas accumulation and other safety accidents. Therefore, such areas must be sealed and filled to ensure the safety and stability of coal mine production activities. Grouting filling and sealing is a common method for treating underground goaf and leftover empty lanes. The selection of filling materials is one of the key factors that directly affect the quality of the project. The filling material needs to have a low dry density, high compressive strength and low cost.
[0004] At present, paste materials are mostly used in related technologies to fill coal mine tunnels. Paste materials are a kind of slurry material with good fluidity and plasticity made by mixing coal gangue, cementitious materials, water, etc. in a certain proportion. However, there are some shortcomings in paste materials. Paste materials have strict requirements on the particle size, gradation and chemical composition of raw materials, and need to be carefully screened and processed. In addition, its preparation process requires special equipment and process flow, including multiple links such as crushing, grinding and stirring of raw materials. The preparation cost is high, and there are certain requirements on the technical level of operators. At the same time, it is difficult to control the setting time and strength of paste materials: although the mechanical properties of paste materials can be adjusted, in actual applications, its setting time and strength growth are affected by many factors, such as temperature, humidity, fluctuations in raw material quality, etc., which makes it difficult to accurately control. If the setting time is too long, it may affect subsequent mining operations; if the strength growth does not meet expectations, it will affect the stability and support effect of the filling body. In addition, during the pipeline transportation process, the paste material will cause certain wear on the inner wall of the pipeline due to its own particle characteristics and high concentration. Long-term use will cause the pipe wall thickness to decrease, and even cause problems such as breakage and leakage. Regular inspection and replacement of pipes are required, which increases maintenance costs and downtime, and affects production efficiency.
[0005] In the field of building materials, foamed cement is widely used due to its light weight, thermal insulation, good mechanical properties and other characteristics. Foamed cement can be used for filling coal mine tunnels. At present, carbon dioxide can be used as the foaming gas to prepare foamed cement materials, but this cement material has the following shortcomings: The physical properties of carbon dioxide make it difficult to accurately control it during the foaming process. Compared with traditional foaming agents, the diffusion rate of carbon dioxide gas is faster, and the formation and stabilization process of bubbles in cement slurry is more complicated. When the consistency, temperature and other conditions of the cement slurry change slightly, the foaming behavior of carbon dioxide may be significantly affected, resulting in uneven bubble size and inconsistent distribution, which in turn affects the overall quality and performance stability of the foamed cement material. Slow early strength development: The early strength growth of foamed cement prepared using carbon dioxide as the foaming gas is relatively slow. This is because when carbon dioxide participates in the cement hydration reaction, the reaction mechanism is different from the traditional hydration process, which will inhibit the early hydration reaction process of cement to a certain extent. For some projects with high requirements for construction progress, insufficient early strength may lead to extended demoulding time, and subsequent processes cannot be carried out in time, affecting the progress of the project and increasing construction costs. Carbon dioxide gas molecules are small, and there is a risk of gas leakage during the hardening process of foamed cement materials. Even after the cement paste has initially solidified, some carbon dioxide gas may still escape from the pores, causing the actual porosity of the foamed cement to be inconsistent with expectations, reducing the thermal insulation and lightening effects of the material. Moreover, gas leakage may also make the internal structure of the foamed cement less dense, affecting its mechanical properties. During the preparation process, factors such as ambient temperature and humidity have a greater impact on the foaming effect of carbon dioxide. In a low temperature environment, the solubility of carbon dioxide increases and the foaming efficiency decreases; in a high humidity environment, moisture may affect the cement paste's adsorption and stabilization effect on carbon dioxide gas, resulting in unstable foaming quality, making the prepared filling material prone to voids during the filling process, affecting the filling effect, reducing the support effect of the filling body, and affecting the stability of the tunnel. Summary of the invention
[0006] The present application provides a coal-based solid waste foamed cement material for filling coal mine tunnels and a preparation method thereof, so as to solve the problem that the filling materials used for filling coal mine tunnels in the prior art are prone to voids during the filling process, affecting the filling effect, reducing the supporting effect of the filling body, and affecting the stability of the tunnel.
[0007] In a first aspect, the present application provides a coal-based solid waste foamed cement material for filling coal mine tunnels, wherein the coal-based solid waste foamed cement material is used for filling coal mine tunnels, and the coal-based solid waste foamed cement material comprises: 10 to 30 parts of coal gasification coarse slag powder, 0 to 30 parts of primary fly ash, 70 to 90 parts of cement, 0.3 to 0.8 parts of foam stabilizer, and 0.1 to 0.5 parts of admixture; wherein the coal-based solid waste foamed cement material is also doped with foam, and the foam dosage is 2 to 5 times the volume of cement slurry,
[0008] The coal gasification coarse slag powder is water-coal slurry furnace gasification coarse slag, and the components of the coal gasification coarse slag powder are as follows by mass percentage: 40% silicon dioxide, 19% aluminum oxide, 15% iron oxide, 16% calcium oxide, 3% sulfur trioxide, 3% sodium oxide, 1% magnesium oxide, 0.5% titanium oxide, and 0.5% potassium oxide.
[0009] In some possible implementations, the dry density of the coal-based solid waste foamed cement material is 300-850 kg / m 3 , 28-day compressive strength is 0.4~2.0MPa.
[0010] In some possible implementations, the dry density of the coal-based solid waste foamed cement material is 360-700 kg / m 3 , 28-day compressive strength is 0.6~1.7MPa.
[0011] In some possible implementations, the water-to-solid ratio of the coal-based solid waste foamed cement material is 0.40 to 0.55.
[0012] In some possible implementations, the foam stabilizer is a modified silicone resin polyether emulsion, and the additive is a polycarboxylic acid water reducer or a naphthalene-based water reducer.
[0013] In some possible implementations, the coal-based solid waste foamed cement material also includes a foaming agent, and the foaming agent is a composite surfactant of fatty alcohol polyoxyethylene sodium sulfate and sodium dodecyl sulfate.
[0014] In a second aspect, the present application provides a method for preparing the coal-based solid waste foamed cement material according to the first aspect, the method comprising:
[0015] The decarbonized coal gasification coarse slag is placed in a ball mill for grinding, and after grinding, it is sieved through a 325-mesh sieve to obtain a raw material of the required particle size, and the coarse coal gasification slag powder is weighed to obtain the fine powder;
[0016] Weigh the required cement and fly ash, and mix them evenly with the coal gasification coarse slag powder in a mixing barrel;
[0017] Weigh the required foaming agent, foam stabilizer, additive, and water, mix them evenly, and prepare water-based foam by a compressed air foaming machine;
[0018] Passing water into the mixing barrel, stirring to obtain mortar, then mixing the water-based foam with the mortar, stirring and mixing to obtain a uniform foam slurry;
[0019] The foam uniform slurry is poured into a 70*70*70 mm mold and smoothed, and the coal-based solid waste foamed cement material is obtained after demoulding and curing.
[0020] In some possible implementations, the decarbonization process of the coal gasification crude slag includes: placing the raw materials in an oven at 400° C. to 600° C. for 4 to 6 hours.
[0021] In some possible implementations, the particle size requirement of the coal gasification coarse slag powder is as follows: the component with a particle size of less than 45 μm accounts for 60-100%.
[0022] In some possible implementations, the curing temperature is 25 to 50° C., and the curing period is 7 to 28 days.
[0023] In some possible implementations, after the water-based foam and the mortar are mixed, the stirring speed is continued to be 300 to 400 r / min, and the stirring time is 1 to 5 minutes.
[0024] From the above content, it can be seen that the present application provides a material for use and a preparation method thereof, wherein the coal-based solid waste foamed cement material is used for filling coal mine tunnels, and the coal-based solid waste foamed cement material comprises: 10 to 30 parts of coal gasification coarse slag powder, 0 to 30 parts of primary fly ash, 70 to 90 parts of cement, 0.3 to 0.8 parts of foam stabilizer, and 0.1 to 0.5 parts of admixture; wherein, the coal-based solid waste foamed cement material is also doped with foam, and the foam dosage is 2 to 5 times the volume of the cement slurry, and the coal gasification coarse slag powder is water-coal slurry furnace gasification coarse slag, and the composition of the coal gasification coarse slag powder is in mass percentage: 40% silicon dioxide, 19% aluminum oxide, 15% iron oxide, 16% calcium oxide, 3% sulfur trioxide, 3% sodium oxide, 1% magnesium oxide, 0.5% titanium oxide, and 0.5% potassium oxide. This application optimizes the foaming process of physical foaming. Through the physical foaming method, coal gasification slag and fly ash can be effectively utilized, the amount of foaming agent can be reduced, and the overall performance of foamed cement can be improved. This application uses the physical foaming method to replace part of the cement with coal-based solid waste as raw materials to prepare a lightweight and high-strength foamed cement material that meets the requirements for underground tunnel filling. DETAILED DESCRIPTION
[0025] The embodiments are described in detail below. The embodiments described in the following embodiments do not represent all embodiments consistent with the present application. They are only examples of systems and methods consistent with some aspects of the present application as detailed in the claims.
[0026] Coal-based solid waste refers to solid waste generated during coal mining, processing and conversion, mainly including coal gangue, coal gasification slag, fly ash, etc. The large-scale storage of these solid wastes not only occupies a large amount of land resources, but also may cause environmental pollution and safety hazards.
[0027] Due to the special mining method used in coal mines, in the process of coal mining, the working face often needs to cross unknown old lanes and leftover cross empty lanes. These goaf areas or working face lanes have extremely high requirements for airtightness. If the management of these old lanes is not sufficient, it may cause water seepage, roof collapse, gas accumulation and other safety accidents. Therefore, such areas must be sealed and filled to ensure the safety and stability of coal mine production activities. Grouting filling and sealing is a common method for treating underground goaf and leftover empty lanes. The selection of filling materials is one of the key factors that directly affect the quality of the project. The filling material needs to have a low dry density, high compressive strength and low cost.
[0028] At present, paste materials are mostly used in related technologies to fill coal mine tunnels. Paste materials are a kind of slurry material with good fluidity and plasticity made by mixing coal gangue, cementitious materials, water, etc. in a certain proportion. However, there are some shortcomings in paste materials. Paste materials have strict requirements on the particle size, gradation and chemical composition of raw materials, and need to be carefully screened and processed. In addition, its preparation process requires special equipment and process flow, including multiple links such as crushing, grinding and stirring of raw materials. The preparation cost is high, and there are certain requirements on the technical level of operators. At the same time, it is difficult to control the setting time and strength of paste materials: although the mechanical properties of paste materials can be adjusted, in actual applications, its setting time and strength growth are affected by many factors, such as temperature, humidity, fluctuations in raw material quality, etc., which makes it difficult to accurately control. If the setting time is too long, it may affect subsequent mining operations; if the strength growth does not meet expectations, it will affect the stability and support effect of the filling body. In addition, during the pipeline transportation process, the paste material will cause certain wear on the inner wall of the pipeline due to its own particle characteristics and high concentration. Long-term use will cause the pipe wall thickness to decrease, and even cause problems such as breakage and leakage. Regular inspection and replacement of pipes are required, which increases maintenance costs and downtime, and affects production efficiency.
[0029] In the field of building materials, foamed cement is widely used because of its light weight, thermal insulation, good mechanical properties and other characteristics. Foamed cement can be used for filling coal mine tunnels. At present, carbon dioxide can be used as the foaming gas to prepare foamed cement materials. The capture and storage of CO2 require high costs for the purchase and maintenance of professional equipment, which not only increases the cost of raw materials, but also limits its large-scale application. Secondly, CO2 has extremely strict requirements for pipeline transportation. Especially when transported under high pressure, the pipeline needs to withstand high pressure and there is a risk of leakage. Compared with the ground working environment, the underground environment is more complex, which further increases the safety protection cost of the operation. Furthermore, CO2 foaming needs to be mixed with a specific foaming agent. This process has more stringent requirements on the preparation process conditions and requires precise control, which usually requires substantial adjustments to the equipment and process. In addition, the physical properties of carbon dioxide make it difficult to accurately control it during the foaming process. Compared with traditional foaming agents, the diffusion rate of carbon dioxide gas is faster, and the formation and stabilization process of bubbles in cement slurry is more complicated. When the consistency, temperature and other conditions of the cement paste change slightly, the foaming behavior of carbon dioxide may be significantly affected, resulting in uneven bubble size and inconsistent distribution, which in turn affects the overall quality and performance stability of the foamed cement material. Slow early strength development: The early strength growth of foamed cement prepared using carbon dioxide as the foaming gas is relatively slow. This is because when carbon dioxide participates in the cement hydration reaction, the reaction mechanism is different from the traditional hydration process, which will inhibit the early hydration reaction of cement to a certain extent. For some projects with high requirements for construction progress, insufficient early strength may lead to extended demoulding time, and subsequent processes cannot be carried out in time, affecting the progress of the project and increasing construction costs. Carbon dioxide gas molecules are small, and there is a risk of gas leakage during the hardening process of foamed cement materials. Even after the cement paste is initially solidified, some carbon dioxide gas may still escape from the pores, resulting in the actual porosity of the foamed cement not meeting expectations, reducing the thermal insulation performance and lightening effect of the material. In addition, gas leakage may also make the internal structure of the foamed cement less dense, affecting its mechanical properties. During the preparation process, factors such as ambient temperature and humidity have a greater impact on the carbon dioxide foaming effect. In a low-temperature environment, the solubility of carbon dioxide increases and the foaming efficiency decreases; in a high-humidity environment, moisture may affect the cement slurry's adsorption and stabilization of carbon dioxide gas, resulting in unstable foaming quality, making the prepared filling material prone to voids during the filling process, affecting the filling effect, reducing the supporting effect of the filling body, and affecting the stability of the tunnel.
[0030] Based on this, the present application provides a coal-based solid waste foamed cement material. The present application optimizes the physical foaming process. Through the physical foaming method, coal gasification slag and fly ash can be effectively utilized, the amount of foaming agent can be reduced, and the overall performance of the foamed cement can be improved. The present application uses the physical foaming method to replace part of the cement with coal-based solid waste as raw materials to prepare a lightweight and high-strength foamed cement material that meets the use requirements of underground tunnel filling.
[0031] In some embodiments, a coal-based solid waste foamed cement material is provided, which is used for filling coal mine tunnels. The coal-based solid waste foamed cement material comprises: 10 to 30 parts of coal gasification coarse slag powder, 0 to 30 parts of primary fly ash, 70 to 90 parts of cement, 0.3 to 0.8 parts of foam stabilizer, and 0.1 to 0.5 parts of admixture; wherein, the coal-based solid waste foamed cement material is also mixed with foam, the foam dosage is 2 to 5 times the volume of cement slurry, and the cement is PO42.5 cement.
[0032] The coal gasification coarse slag powder is water-coal slurry furnace gasification coarse slag, and the components of the coal gasification coarse slag powder are as follows by mass percentage: 40% silicon dioxide, 19% aluminum oxide, 15% iron oxide, 16% calcium oxide, 3% sulfur trioxide, 3% sodium oxide, 1% magnesium oxide, 0.5% titanium oxide, and 0.5% potassium oxide.
[0033] In some embodiments, the dry density of the coal-based solid waste foamed cement material is 300-850 kg / m 3 , 28-day compressive strength 0.4~2.0MPa
[0034] In some embodiments, the dry density of the coal-based solid waste foamed cement material is 360-700 kg / m 3 , 28-day compressive strength is 0.6~1.7MPa.
[0035] In some embodiments, the water-to-solid ratio of the coal-based solid waste foamed cement material is 0.40-0.55.
[0036] In some embodiments, the foam stabilizer is a modified silicone resin polyether emulsion, and the additive is a polycarboxylic acid water reducer or a naphthalene-based water reducer.
[0037] In some embodiments, the coal-based solid waste foamed cement material further includes a foaming agent, and the foaming agent is a composite surfactant of fatty alcohol polyoxyethylene ether sodium sulfate and sodium dodecyl sulfate.
[0038] In some embodiments, the method for preparing the coal-based solid waste foamed cement material comprises:
[0039] The decarbonized coal gasification coarse slag is placed in a ball mill for grinding, and after grinding, it is sieved through a 325-mesh sieve to obtain a raw material of the required particle size, and the coarse coal gasification slag powder is weighed to obtain the fine powder;
[0040] Weigh the required cement and fly ash, and mix them evenly with the coal gasification coarse slag powder in a mixing barrel;
[0041] Weigh the required foaming agent, foam stabilizer, additive, and water, mix them evenly, and prepare water-based foam by a compressed air foaming machine;
[0042] Passing water into the mixing barrel, stirring to obtain mortar, then mixing the water-based foam with the mortar, stirring and mixing to obtain a uniform foam slurry;
[0043] The foam uniform slurry is poured into a 70*70*70 mm mold and smoothed, and the coal-based solid waste foamed cement material is obtained after demoulding and curing.
[0044] In some embodiments, the decarbonization process of the coal gasification crude slag includes: placing the raw materials in an oven at 400° C. to 600° C. for 4 to 6 hours.
[0045] In some embodiments, the particle size requirement of the coal gasification coarse slag powder is as follows: the component with a particle size of less than 45 μm accounts for 60-100%.
[0046] In some embodiments, the curing temperature is 25-50° C., and the curing period is 7-28 days.
[0047] In some embodiments, the water-based foam and the mortar are mixed and then stirred at a speed of 300 to 400 rpm.
[0048] 400r / min, stirring time is 1 to 5min.
[0049] The present application uses coal-based solid waste as raw material and utilizes a physical foaming method to prepare a coal-based solid waste foamed cement material for coal mine tunnel filling, which brings the following technical effects:
[0050] Improve resource utilization: Coal-based solid waste contains various components such as silicon dioxide, aluminum oxide, and iron oxide. After proper treatment and processing, these components can be used as alternative raw materials for cement. Using coal-based solid waste to prepare foamed cement materials can effectively reduce the accumulation of coal-based solid waste, reduce the occupation of land resources, and realize the resource utilization of solid waste, which is in line with the concept of sustainable development.
[0051] Reduce production costs: Coal-based solid waste is a kind of waste with relatively low acquisition cost. When preparing foamed cement materials, using coal-based solid waste to replace part of cement can reduce the amount of cement used. Cement production is a high-energy consumption industry with relatively high prices. Therefore, it can reduce the cost of raw materials, thereby reducing the overall production cost and improving economic benefits.
[0052] Improve the lightweight characteristics of materials: By introducing a large number of evenly distributed bubbles through the physical foaming method, the density of the foamed cement material is significantly reduced, forming a lightweight structure. This is of great significance for coal mine tunnel filling. On the one hand, it can reduce the weight of the filling body, reduce the additional pressure on the tunnel surrounding rock, and reduce the difficulty and cost of tunnel support; on the other hand, lightweight filling materials are more convenient for transportation and construction operations.
[0053] Enhanced thermal insulation performance: The presence of a large number of bubbles forms numerous closed pores inside the foamed cement material, which can effectively prevent the transfer of heat and have good thermal insulation performance. In coal mine tunnels, this thermal insulation performance can reduce heat loss or heat accumulation in the tunnel, help maintain a relatively stable temperature environment in the tunnel, and improve working conditions.
[0054] Improve the sound insulation performance of the material: The closed pore structure can not only insulate, but also effectively absorb and block the propagation of sound. Therefore, the coal-based solid waste foamed cement material has a good sound insulation effect. In coal mine tunnels, it can reduce the impact of noise generated by the operation of mechanical equipment on the surrounding environment and workers.
[0055] Good fluidity and construction performance: The foamed cement material prepared by the physical foaming method usually has good fluidity, which can be more conveniently pumped and poured in the tunnel, filling into complex spaces and corners, improving construction efficiency and filling quality. At the same time, the material has strong plasticity and can adapt to tunnel sections of different shapes and sizes, ensuring the density and integrity of the filling.
[0056] Certain strength and durability: Although the density of coal-based solid waste foamed cement material is low, it can still have the strength to meet the filling requirements of coal mine tunnels through reasonable formula design and process control. In addition, some components in coal-based solid waste may react with cement during the hydration process to generate some gelling substances, further improving the strength and durability of the material and ensuring the stability of the filling body during long-term use.
[0057] This application uses coal-based solid waste as one of the main raw materials to realize its resource utilization, reduce environmental pollution and land occupation, and promote the sustainable development of the coal chemical industry. Using the physical foaming method, a lightweight and high-strength foamed cement material is prepared to meet the requirements for filling underground tunnels. Through the physical foaming method, the foaming process is optimized, the amount of foaming agent is reduced, and the overall performance of the foamed cement is improved. The scheme disclosed in this application helps to improve the utilization efficiency of coal-based solid waste, reduce environmental pollution, and at the same time, reduce the amount of cement raw materials used, which helps to promote energy conservation and emission reduction.
[0058] Example 1
[0059] This embodiment provides a coal-based solid waste foamed cement material for filling coal mine tunnels. The foamed cement material is obtained by the following steps:
[0060] (1) Put the gasified slag into an oven at 500°C for 6 hours, cool it to room temperature naturally, take it out, put it into a ball mill, grind it, and pass it through a 325-mesh sieve. The particle size distribution of the gasified ash is D10 = 2.49 μm, D50 = 17.0 μm, and D90 = 76.8 μm. Weigh 80 g of the gasified slag powder;
[0061] (2) Weigh 900 g of cement and 20 g of fly ash, i.e., the coal solid waste content is 10%, and mix them evenly with the gasified coarse slag powder in (1) in a mixing tank;
[0062] (3) Weigh 10 g of a fatty alcohol polyoxyethylene ether sodium sulfate (AES)-sodium dodecyl sulfate (SDS) composite foaming agent, 6 g of a modified silicone resin polyether emulsion foam stabilizer, 5 g of an admixture polycarboxylic acid water reducer, and 500 g of water, mix them evenly, and prepare a stable water-based foam with a fine bubble structure through a compressed air foaming machine.
[0063] (4) slowly adding part of the water obtained in step (3) into the mixing bucket in step (2), stirring for 2 minutes to obtain a uniform mortar; then mixing the prefabricated foam in step (3) with the mortar, with the foam volume: mortar volume = 2:1, stirring for 1 minute, and mixing to obtain a foam uniform slurry with a certain fluidity;
[0064] (5) The uniform slurry obtained in step (4) is poured into a 70*70*70 mm mold and smoothed. After demolding and curing, a solid waste-based foamed cement material test block is obtained.
[0065] Wherein, the water-to-solid ratio in step (4) is 0.42, and the rotation speed of the stirrer is 300 r / min.
[0066] According to JG / T266-2011 "Foamed Concrete" and GB / T 43487-2023 "Test Methods for Foamed Concrete and Its Products", the dry density and compressive strength of the test block in step (5) were tested. The dry density was 450 kg / m 3 , 7d strength is 0.67MPa, and 28d strength is 1.1MPa.
[0067] Embodiment 2:
[0068] The difference from Example 1 is that 100 g of gasified coarse slag powder, 100 g of fly ash, and 800 g of cement are weighed, that is, the coal solid waste content is 20%, the water-solid ratio in step (4) is 0.47, and the rest of the preparation process is the same as Example 1. The dry density of the test block is 700 kg / m 3, 7d strength is 1.55MPa, and 28d strength is 1.70MPa.
[0069] Embodiment 3:
[0070] The difference from Example 1 is that 100 g of gasified coarse slag powder, 100 g of fly ash, and 800 g of cement are weighed, that is, the coal solid waste content is 20%, the foam volume in step (4): mortar volume = 3:1, the water-solid ratio is 0.52, and the rest of the preparation process is the same as Example 1. The dry density of the test block is 360 kg / m 3 , 7d strength is 0.51MPa, and 28d strength is 0.65MPa.
[0071] Embodiment 4:
[0072] The difference from Example 1 is that 200g of gasified coarse slag powder, 100g of fly ash, and 700g of cement are weighed, that is, the coal solid waste content is 30%, and in step (4), the foam volume: mortar volume = 4:1, and the water-solid ratio is 0.47. The dry density of the test block is 420kg / m 3 , 7d strength is 0.55MPa, and 28d strength is 0.67MPa.
[0073] Comparative Example 1:
[0074] The difference from Example 1 is that the foam volume in step (4) is adjusted to 5:1 for the mortar volume, and the rest of the preparation process is the same as that of Example 1. The prepared test block collapsed and could not be formed.
[0075] Comparative Example 2:
[0076] The difference from Example 4 is that the addition of the foam stabilizer and the admixture is omitted, and the rest of the preparation process is the same as that of Example 4. The prepared test block collapsed and could not be formed.
[0077] The formulas and related properties of each group of embodiments and comparative examples are summarized in Table 1.
[0078] Table 1
[0079]
[0080] It can be seen from the relevant data of Comparative Example 1 in Table 1 that when the foam content is increased to 5 times the volume of cement slurry, the test block collapses. This is because the foam volume accounts for too large a proportion, and a small amount of cement cannot complete the hydration reaction, so the molding fails. It can be seen from the relevant data of Comparative Example 2 that if the foam stabilizer and admixture are not added, the prepared foam cannot exist stably, and a large amount of foam will burst when mixed with cement slurry, causing the test block to collapse. The corresponding relationship between the dry density and compressive strength of each group of test blocks in Examples 1 to 4 meets the corresponding requirements in JG / T266-2011 "Foamed Concrete".
[0081] The present application provides a method for preparing coal-based solid waste foamed cement. The dry density and compressive strength of the test block are tested according to JG / T266-2011 "Foamed Concrete" and GB / T 43487-2023 "Test Methods for Foamed Concrete and Products". The dry density of the foamed cement test block of the present invention is 450kg / m 3 The 7d strength is 0.67MPa and the 28d strength is 1.1MPa. Its mechanical properties meet the use requirements, with large slag consumption, low cost and simple process, providing a new way for the effective disposal and efficient utilization of coal-based solid waste.
[0082] It can be seen from the above embodiments that the present application provides a coal-based solid waste foamed cement material for filling coal mine tunnels and a preparation method thereof. The coal-based solid waste foamed cement material is used for filling coal mine tunnels, and the coal-based solid waste foamed cement material includes: 10 to 30 parts of coal gasification coarse slag powder, 0 to 30 parts of primary fly ash, 70 to 90 parts of cement, 0.3 to 0.8 parts of foam stabilizer, and 0.1 to 0.5 parts of admixture; wherein, the coal-based solid waste foamed cement material is also doped with foam, and the foam dosage is 2 to 5 times the volume of the cement slurry, and the coal gasification coarse slag powder is water-coal slurry furnace gasification coarse slag, and the composition of the coal gasification coarse slag powder is calculated by mass percentage as follows: 40% silicon dioxide, 19% aluminum oxide, 15% iron oxide, 16% calcium oxide, 3% sulfur trioxide, 3% sodium oxide, 1% magnesium oxide, 0.5% titanium oxide, and 0.5% potassium oxide. This application optimizes the foaming process of physical foaming. Through the physical foaming method, coal gasification slag and fly ash can be effectively utilized, the amount of foaming agent can be reduced, and the overall performance of foamed cement can be improved. This application uses the physical foaming method to replace part of the cement with coal-based solid waste as raw materials to prepare a lightweight and high-strength foamed cement material that meets the requirements for underground tunnel filling.
[0083] Similar parts between the embodiments provided in this application can be referenced to each other. The specific implementation methods provided above are only a few examples under the general concept of this application and do not constitute a limitation on the protection scope of this application. For those skilled in the art, any other implementation methods expanded based on the scheme of this application without creative work belong to the protection scope of this application.
Claims
1. A coal-based solid waste foamed cement material for filling coal mine tunnels, characterized in that: The coal-based solid waste foamed cement material comprises: 10 to 30 parts of coal gasification coarse slag powder, 0 to 30 parts of primary fly ash, 70 to 90 parts of cement, 0.3 to 0.8 parts of foam stabilizer, and 0.1 to 0.5 parts of admixture; wherein, the coal-based solid waste foamed cement material is also mixed with foam, and the foam content is 2 to 5 times the volume of cement slurry. The coal gasification coarse slag powder is water-coal slurry furnace gasification coarse slag, and the components of the coal gasification coarse slag powder are as follows by mass percentage: 40% silicon dioxide, 19% aluminum oxide, 15% iron oxide, 16% calcium oxide, 3% sulfur trioxide, 3% sodium oxide, 1% magnesium oxide, 0.5% titanium oxide, and 0.5% potassium oxide.
2. The coal-based solid waste foamed cement material for coal mine tunnel filling according to claim 1, characterized in that: The dry density of the coal-based solid waste foamed cement material is 300-850 kg / m 3 , 28-day compressive strength is 0.4~2.0MPa.
3. The coal-based solid waste foamed cement material for coal mine tunnel filling according to claim 1, characterized in that: The water-to-solid ratio of the coal-based solid waste foamed cement material is 0.40-0.
55.
4. The coal-based solid waste foamed cement material for coal mine tunnel filling according to claim 1, characterized in that: The foam stabilizer is a modified silicone resin polyether emulsion, and the additive is a polycarboxylic acid water reducer or a naphthalene-based water reducer.
5. The coal-based solid waste foamed cement material for coal mine tunnel filling according to claim 1, characterized in that: The coal-based solid waste foamed cement material also includes a foaming agent, and the foaming agent is a fatty alcohol polyoxyethylene ether sodium sulfate and sodium dodecyl sulfate composite surfactant.
6. A method for preparing a coal-based solid waste foamed cement material for filling coal mine tunnels, characterized in that: The method comprises: The decarbonized coal gasification coarse slag is placed in a ball mill for grinding, and after grinding, it is sieved through a 325-mesh sieve to obtain a raw material of the required particle size, and the coarse coal gasification slag powder is weighed to obtain the fine powder; Weigh the required cement and fly ash, and mix them evenly with the coal gasification coarse slag powder in a mixing barrel; Weigh the required foaming agent, foam stabilizer, additive, and water, mix them evenly, and prepare water-based foam by a compressed air foaming machine; Passing water into the mixing barrel, stirring to obtain mortar, then mixing the water-based foam with the mortar, stirring and mixing to obtain a uniform foam slurry; The foam uniform slurry is poured into a 70*70*70 mm mold and smoothed, and the coal-based solid waste foamed cement material is obtained after demoulding and curing.
7. The method for preparing the coal-based solid waste foamed cement material for coal mine tunnel filling according to claim 6, characterized in that: The decarbonization process of the coal gasification coarse slag comprises: placing the raw materials in an oven at 400° C. to 600° C. for 4 to 6 hours.
8. The method for preparing the coal-based solid waste foamed cement material for coal mine tunnel filling according to claim 6, characterized in that: The particle size requirement of the coal gasification coarse slag powder is: the component with a particle size of less than 45 μm accounts for 60-100%.
9. The method for preparing the coal-based solid waste foamed cement material for coal mine tunnel filling according to claim 6, characterized in that: The curing temperature is 25-50°C and the curing period is 7-28 days.
10. The method for preparing the coal-based solid waste foamed cement material for coal mine tunnel filling according to claim 6, characterized in that: After the water-based foam and the mortar are mixed, the stirring speed is continued to be 300-400 r / min, and the stirring time is 1-5 min.
Citation Information
Cited By
Function gradient material based on coal-based solid waste and high roof contact rate filling method
CN121872705A